Salsipaludibacter albus gen. nov., sp. nov., a novel actinobacterial strain isolate from a Portuguese solar saltern and proposal of Salsipaludibacteraceae fam. nov. and Salsipaludibacterales ord. nov. Issue 2 (9th February 2022) - Almeida, Eduarda; Henriques, Valentina; Wiegand, Sandra; Albuquerque, Luciana; Schumann, Peter; Kohn, Timo; Jogler, Christian; Simões da Costa, Milton; Lobo-da-Cunha, Alexandre; de Fátima Carvalho, Maria; Lage, Olga Maria
Abstract : A novel micro-organism designated AS10 T was isolated from dry salt collected from Aveiro saltern in the north of Portugal. Cells were Gram-stain-positive, non-motile, non-endospore-forming, rod-shaped and aerobic. Strain AS10 T was characterized by long filaments of rod-shaped cells, presenting also coccoid cellular forms at the end of the filaments, unveiling some pleomorphism. Rod-shaped cells varied from 0.3 to 0.6 µm wide and from 0.6 to 2 µm long. Growth of AS10 T occurred at 15–40 °C (optimum, 20–30 °C), 0–10% (w/v) NaCl (optimum, 2%) and pH 4.5–11.0 (optimum, pH 8.0–11.0). The peptidoglycan type was A1ϒ-type with 3-hydroxy-diaminopimelic acid. The major fatty acids were C16:0, iso-C14:0, C17:0 and C14:0 . The major respiratory quinone was MK-9(H4 ). Phylogenetic analysis based on 16S rRNA gene sequences showed that strain AS10 T was similar to actinobacterial members of the class Nitriliruptoria, with Nitriliruptor alkaliphilus ANL-iso2 T being the closest relative the species with a sequence pairwise similarity of 91.21%. Average nucleotide identity, average amino acid identity and in silico DNA–DNA hybridization values between strain AS10 T and N. alkaliphilus ANL-iso2 T were 71.34, 53.57 and 18.90%, respectively. The genome DNA G+C content of AS10 T was 71.8 mol%. Based on genomic, phylogenetic, phenotypic and chemotaxonomic studies, we describe a new species of a novel genus represented by strain AS10 T (=LMG 31937 T =CECT 30148 T ) for which we propose the name Salsipaludibacter albus gen. nov., sp. nov. We also propose that this organism represents a new family named Salsipaludibacteraceae fam. nov. of a novel order named Salsipaludibacterales ord. nov.